Effects of rubidium on responses to potassium channel openers in rat isolated aorta - Greenwood, I A; Weston, A H (British journal of pharmacology, 1993)
1. In a physiological salt solution (PSS) in which potassium (K) was replaced by rubidium (Rb), segments of rat aorta precontracted with 20 mM RbCl were fully relaxed by K-channel openers with an order of potency levcromakalim > cromakalim > aprikalim > RP 49356. These relaxations were inhibited by glibenclamide. 2. Segments of rat aorta bathed in normal PSS and precontracted with 20 mM KCl were also relaxed by these K-channel openers with an order of potency levcromakalim > cromakalim > aprikalim > RP 49356. These relaxations were glibenclamide-sensitive. However, the absolute potencies of the K-channel openers were approximately four times greater in normal PSS than in RbPSS. 3. In RbPSS, minoxidil sulphate relaxed segments of aorta precontracted with 20 mM RbCl by approximately 20% whereas in normal PSS it fully relaxed those contracted with 20 mM KCl. 4. In RbPSS, levcromakalim-induced relaxation of aortic segments precontracted with 20 mM RbCl was initially well-maintained but then faded by approximately 60% of the initial relaxation to a new, stable level. Subsequent exposure to RP 49356 or to higher concentrations of levcromakalim was without further relaxant effect. Similar changes were observed when RP 49356 was the initial relaxant and tissues were exposed to either RP 49356 or levcromakalim. In normal PSS, levcromakalim- or RP 49356-induced relaxation of contractions produced by 20 mM KCl was well-maintained. 5. In RbPSS, minoxidil sulphate-induced relaxation of aortic segments precontracted with 20 mM RbCl was well-maintained. Subsequent exposure to either levcromakalim or to RP 49356 produced further tissue relaxation. 6. In RbPSS, levcromakalim produced no detectable increase in either 86Rb- or 42K-efflux from rat aortic strips. In normal PSS, a significant increase in the exchange of both isotopes was detected.7. Levcromakalim hyperpolarized segments of rat aorta bathed both in normal PSS and after depolarization by the addition of 20 mM KCI. Exposure to RbPSS depolarized the tissue and under these conditions, levcromakalim had no effect on membrane potential.8. In Rb- and normal PSS, levcromakalim produced a similar degree of inhibition of the refilling of then or adrenaline-sensitive Ca store.9. It is concluded that millimolar concentrations of Rb inhibit the plasmalemmal ATP-sensitive K-channels (KATP) which are the target of the K-channel openers. The relaxant actions of the K-channel openers in both normal and Rb-PSS and the inhibition of these effects by glibenclamide may reflect a functional interaction between these agents at ATP-binding sites associated with both KATP and with intracellular structures including Ca stores.